PUBLIC SMOKING (Tufts Archival Research Center, 2007)
Report providing background on smoking restriction activity in an attempt to address indoor air quality and environmental tobacco smoke in terms of public smoking. States objective of discouraging both unnecessary smoking restrictions and discrimination against smokers. Details strategies, goals and tactics at both the federal and state levels in addressing the public smoking issue from the tobacco industry's standpoint.